Isolation of Flavonoids from Anaphalis Busua and their Antibacterial Activity - Rajbhandari, M.; Lindequist, U. (Journal of Institute of Science and Technology, 2020)
Anaphalis busua (Buch-Ham ex D. Don) is traditionally used to treat cuts and wounds. In the agar dilution method, the hexane extract of the aerial part of A. busua exhibited potent antibacterial activity with a minimal inhibitory concentration of 25 μg/ml against Bacillus subtilis and 500 μg/ml against Staphylococcus aureus. For the isolation of antibacterial compounds, the hexane extract was fractionated by silica gel and Sephadex LH 20 column chromatography. The direct bioautography method was used to determine the antibacterial activity of the fractions. The active fractions were finally purified by semi-preparative HPLC on C18 Phenomenex column under gradient condition. Four flavones derivatives of 3,5-dihydroxy-6,7,8-trimethoxyflavone (1), 3,5,7-trihydroxy-6-methoxyflavone (alnusin) (2), 3,5,7-trihydroxy-8-methoxyflavone (3) and pinocembrin (4) were isolated, and their structures were established by 1H, 13C, DEPT-135, and ESI-MS spectroscopy. These compounds were isolated for the first time from A. busua. The fatty acid profile of the hexane extract was analyzed by gas chromatography-mass spectrometry (GC-MS) by silylation with N-methyl-N-trimethylsilyl-trifluoro-acetamide. Pinocembrin showed antibacterial activity with the minimum inhibitory concentration of 60 μg/mL against Bacillus subtilis and 420 μg/mL against Staphylococcus aureus.